Odpowiedzi

2009-10-17T14:38:23+02:00
9/2x - 3y = 48
3/2x +y = 11 ( pomnóż całe wyrarzenie przez -3)

9/2x -3y = 48
-9/2x -3y = -33

dodaj stronami
9/2x - 9/2x - 3y -3y = 48 - 33
- 6y = 15
y = - 15/6
y = - 5/3

9/2x - 3 razy - 5/3 = 48
9/2x +5 = 48
9 + 10x = 48x
9 = 48x-10x
9 = 38x
x = 9/38
1 5 1
2009-10-17T14:41:01+02:00
9/2x - 3y = 48
3/2x + y = 11

9/2x - 3y = 48
3/2x + y = 11 | × 3

9/2x - 3y = 48
3/2x × 3 + 3y = 3 × 11

9/2x - 3y = 48
9/2x +3y = 33
-----------------
Dodajemy stronami:
-3y +3y+ 9/2x+9/2x= 48+33
18/2x=81
9x=81|÷9
x= 9

Podstawiamy do górnego wzoru: (obojętnie którego)
3/2x + y = 11
3/2 × 9 +y = 11
27/2 + y=11
y= 11- 27/2
y=11-13 ½
y= -2 ½
1 5 1
2009-10-17T17:15:49+02:00
9/2x - 3y = 48
3/2x + y = 11 /* 3

9/2x- 3y= 48
9/2x+ 3y= 33

18/2x=15/*x
9=15x
x=9/15

x=9/15
3/2*9/15 + y= 1

x=9/15
15/6+ y= 1

x= 9/15
y=- 9/6
1 5 1